Dynamic response of laminated composites using design of experiments: An experimental and numerical study - dos Santos Souza L.F.* (2019)
© 2018 Elsevier LtdIn addition to many advantages, composite materials constitute a new challenge in many industrial fields and applications. Vibration Based Methods (VBM) are relatively simple and at low cost to detect damage and fails in composite structures, but they are sensitive to variations in geometry and material properties. Recently, the main challenge in VBM is to establish a robust process to be applied on an industrial environment. In this work, a methodology to identify the effect of design parameters on the dynamic response of laminated composite plates is presented. For the case of composite materials, the production process plays an important role. Numerical dynamic analyses are run using the Finite Element code ABAQUS™ which is complemented with user subroutines written in Fortran and Python. A Design of Experiments (DoE) strategy is developed to reduce the number of experiments and to evaluate the effect of the design parameters. Two sets of composite plates were evaluated, [0]8 and [0/−15/15/0/−15/15]s, with natural frequencies used as response quantities. In addition, Frequency Response Functions are analyzed, as they are obtained by a full factorial design. Afterwards, the results are discussed with proper attention for the potential and for the limitations of the proposed methodology from the perspective of usage to detect damage and failure in composite structures.